2008
DOI: 10.1080/00498250701851891
|View full text |Cite
|
Sign up to set email alerts
|

In vivoapproach for the evaluation of mechanism-based inhibition of cytochrome P450 3A in rats

Abstract: 1. There have been no reports showing that the area under the concentration-time curve (AUC) of a probe drug is elevated due to mechanism-based inhibition (MBI) of drug-metabolizing enzymes in animals. This study ascertained that mechanism-based inhibitors reported to induce drug-drug interactions (DDIs) in humans also caused MBI in rats. 2. Midazolam (MDZ), mainly metabolized by cytochrome P450 3A in rats, and mibefradil, which showed the most intense time-dependent inhibition among the inhibitors tested, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Therefore, we aimed to quantitatively predict the DDI observed in rats using a PBPK model from in vitro inactivation parameters in this study. Although it was suggested that MDZ was mainly metabolized by CYP3A in rats (Sekiguchi et al, 2008), not only CYP3A but also CYP2C isozymes were reported to produce metabolites of MDZ in rats (Chovan et al, 2007). Therefore, there is a possibility that CYP2C isozymes are also inactivated by mibefradil.…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…Therefore, we aimed to quantitatively predict the DDI observed in rats using a PBPK model from in vitro inactivation parameters in this study. Although it was suggested that MDZ was mainly metabolized by CYP3A in rats (Sekiguchi et al, 2008), not only CYP3A but also CYP2C isozymes were reported to produce metabolites of MDZ in rats (Chovan et al, 2007). Therefore, there is a possibility that CYP2C isozymes are also inactivated by mibefradil.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, gastrointestinal absorption is assumed to be described by a first-order rate constant. Plasma concentrations of MDZ from the literature (Sekiguchi et al, 2008) and mibefradil measured by the procedure described above when they were administered solely (E act ϭ E 0 ) were fitted into the PBPK model described above, and CL int, S , CL int, I , k a, S , k a, I , V sys, S , and V sys, I were calculated using SAAM II (version 1.2; Saam Institute, Inc., Seattle, WA). The differential equation for E act can be described as follows (eq.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations